“Translated” or “Transformed”: The Use of Western Hymns in the Evangelization of the Lisu of Southwest China - Arrington, Aminta (Religions, 2021)
Translated western hymns have a bad reputation in missiology. The term “translated” seems to convey a less than authentic expression of Christian faith. However, that was not how it happened when the Lisu of southwest China were evangelized by missionaries from the China Inland Mission in the 1920s and 1930s. The Lisu people exerted much more agency over their translated western hymns than the term “translated” implies. While the kernel of melody and message remained intact, four-part harmonies replaced unison singing. A cappella replaced piano or organ accompaniment. Phrases meaningful in a Victorian context were transformed into phrases meaningful in a Lisu mountain context. Abstract theological terms were replaced by concrete phrases. Western rhyming schemes were laid aside and Lisu poetic couplets were used instead. The end result is that in the everyday arena, in the practical living out of what it means to be a Christian for a communal and still largely oral-preference people such as the Lisu, the Lisu Christian hymns are the centerpiece of worship and devotion, of prayer and penitence. In other words, in the process of cross-cultural transmission, the Lisu hymns were not so much translated, as they were transformed.